Nepal : 2010 Article IV Consultation and Request for Disbursement Under the Rapid Credit Facility; Staff Report; Staff Supplements; Public Information Notice on the Executive Board Discussion; Press Release on the Executive Board Discussion; and Statement by the Alternate Executive Director and Advisor for Nepal. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
After years of macroeconomic stability, the global crisis is having a substantial, albeit somewhat delayed, impact on Nepal's economy and exposing its structural weaknesses. Although the Nepalese rupee appears modestly overvalued, maintaining the peg should remain a key near-term policy objective. Risks in the financial sector are coming to a head and need to be addressed urgently. The Nepal Rastra Bank (NRB)'s recent directives are welcome, but enforcement is crucial to their effectiveness. Bank licensing policy needs to be tightened, banking sector consolidation incentivized, and state-controlled bank reform tackled.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet